2011
DOI: 10.3329/jhpn.v29i3.7869
|View full text |Cite
|
Sign up to set email alerts
|

Is International or Asian Criteria-based Body Mass Index Associated with Maternal Anaemia, Low Birthweight, and Preterm Births among Thai Population? - An Observational Study

Abstract: An observational study was conducted in the four southernmost provinces of Thailand aiming at determining the effect of international or Asian criteria-based body mass index (BMI) in predicting maternal anaemia, low birthweight (LBW), and preterm births among pregnant Thai women and the change in haemoglobin (Hb) level during pregnancy. Maternal anaemia was defined as a haemoglobin (Hb) level of <11 g/dL. Anaemia was detected in 27.4% and 26.9% of 1,192 pregnant women at their first prenatal visit and the thir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 25 publications
4
32
0
Order By: Relevance
“…Our study showed that the average value of BMI in the 1st trimester of pregnant women is 22.7 kg.m −2 . This is consistent with Liabsuetrakul T et al8 ) , who studied 485 pregnant women, aged between 13–46 years with a gestational age of < 14 weeks, and reported their average value of BMI was about 22.4 kg.m −2 . In contrast, more than 50% of pregnant women in the United States have a BMI greater than 25.13 kg.m −2 9 ) .…”
Section: Discussionsupporting
confidence: 89%
“…Our study showed that the average value of BMI in the 1st trimester of pregnant women is 22.7 kg.m −2 . This is consistent with Liabsuetrakul T et al8 ) , who studied 485 pregnant women, aged between 13–46 years with a gestational age of < 14 weeks, and reported their average value of BMI was about 22.4 kg.m −2 . In contrast, more than 50% of pregnant women in the United States have a BMI greater than 25.13 kg.m −2 9 ) .…”
Section: Discussionsupporting
confidence: 89%
“…There were 34 prospective cohorts and eight retrospective cohorts. Of the 42 studies, 16 reported preterm birth , 18 low birthweight , seven small for gestational age , five stillbirth , 19 gestational diabetes , nine pregnancy‐induced hypertension , nine pre‐eclampsia , 10 caesarean delivery , three post‐partum haemorrhage and two perinatal mortality . The study‐specific proportion of BMI and events by perinatal and maternal health outcomes are presented in Supporting Information http://onlinelibrary.wiley.com/doi/10.1111/obr.12293/suppinfo.…”
Section: Resultsmentioning
confidence: 99%
“…There were 34 prospective cohorts and eight retrospective cohorts. Of the 42 studies, 16 reported preterm birth (5,9,10,(13)(14)(15)(16)(38)(39)(40)(41)(42)(43)(44)(45)(46), 18 low birthweight (7,10,11,14,15,39,(41)(42)(43)(44)(45)(47)(48)(49)(50)(51)(52)(53), seven small for gestational age (9,17,39,41,44,54,55), five stillbirth (9,15,16,44,56), 19 gestational diabetes (5,6,9,12,13,…”
Section: Study Characteristicsmentioning
confidence: 99%
“…When examining other factors possibly influencing the development of anemia in pregnancy, published reports have indicated that conditions such as the women's age, 19 education status, 20 nutritional habits, [6] smoking status [21], gravidity [22], parity [23], and the interval between consecutive pregnancies [24] may play a role.…”
Section: Discussionmentioning
confidence: 99%